ChemInform Abstract: Facile Synthesis of P‐Doped Carbon Quantum Dots with Highly Efficient Photoluminescence. Issue 26 (1st July 2014) - Zhou, Jin; Shan, Xiaoyue; Ma, Juanjuan; Gu, Yamin; Qian, Zhaosheng; Chen, Jianrong; Feng, Hui
Abstract P‐doped C quantum dots (PCQDs) are prepared by solvothermal reaction of PBr3 and hydroquinone in the presence of NaOH in Me2CO (autoclave, 200 °C, 1 h).